Eksplorasi Strategi Promosi dari Word of Mouth Ke Tiktok dan Whatsapp dalam Mendorong Minat Beli Konsumen pada UD. Sumber Rejeki - Putri Uswatun Hasanah; Ahmad Dzulfikri Budi Kusworo (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to explore the promotional strategies implemented by UD. Sumber Rejeki and identify opportunities for shifting from word of mouth to digital media, particularly TikTok and WhatsApp, to increase consumer purchasing interest. The study employed a qualitative approach with an exploratory design. Subjects were selected through purposive sampling, including business owners, employees involved in the production and marketing processes, and consumers who had purchased UD. Sumber Rejeki products. Data were collected through in-depth interviews, direct observation of promotional and production activities, and supporting documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation of sources, techniques, and time. The results showed that the promotional strategy is still dominated by word of mouth, which is effective in building consumer trust but less than optimal in expanding market reach. The main obstacles in developing digital promotions include limited digital literacy, human resources, and the lack of systematic promotional planning. However, manual production processes have the potential to create engaging visual content, and WhatsApp has the potential to be developed as a marketing medium. This study concludes that the integration of word of mouth and digital marketing can be an effective strategy to increase business competitiveness.